An Adiabatic-Expansion-Induced Perturbation Study on Gas–Aerosol Partitioning in Ambient Air—Formation of NH4NO3 and Microdroplet Nitrogen Fixation (2) - Yating Gao; Qinchu Fan; Yujiao Zhu; Hengqing Shen; Qi Yuan; Yang Gao; Huiwang Gao; Xiaohong Yao (Atmosphere)
Recent observations have increasingly challenged the conventional understanding of atmospheric NH3 and its potential sources in remote environments. Laboratory studies suggest that the microdroplet redox generation of NH3 could offer an alternative explanation. However, key questions remain: (1) Can microdroplet redox generation of NH3 occur in ambient air? (2) Is it restricted by the presence of specific catalysts? (3) What factors determine the efficiency of ambient NH3 generation via microdroplet redox reactions? We investigate these questions based on adiabatic-expansion-induced perturbation observations performed in various atmospheres over the last decade. Our results indicate the adiabatic-expansion-induced generation of NH3 + HNO3 at ultrafast formation rates, with campaign-dependent stable stoichiometric ratios of HNO3 to NH3, as well as highly variable occurrence frequencies and efficiencies. These findings suggest that microdroplet redox reactions are more likely responsible for the generation of NH3 + HNO3 than conventional atmospheric NH3 chemistry. Moreover, our analysis suggests that the line speed of microdroplets may be one of the key factors in determining the occurrence, stoichiometric ratio and efficiency of the redox reaction. Additionally, the presence of sea salt aerosols and low ambient temperature, rather than the specific catalysts, may significantly influence these processes. However, the current observational data do not allow us to derive a functional relationship between the redox reaction rate and these parameters, nor to fully detail the underlying chemistry. Comprehensive and controlled laboratory experiments, similar to our adiabatic-expansion-induced observations but utilizing state-of-the-art highly sensitive analyzers, would be necessary, though such experiments are beyond our current capabilities.